Antioxidant Activity Test of Effervescent Granules Morinda citrifolia L Leaf Extract with DPPH Free Radical Absorption Method - Muthmainah Tuldjanah; Niluh Puspita Dewi; Dian Rahmawati (Journal of Tropical Pharmacy and Chemistry, 2021)
Morinda citrifolia. L leaf is a plant that has the potential as an antioxidant due to the presence of compounds in the form of flavonoids and other phenolic compounds that can function as natural antioxidants. In connection with this, research was carried out to Morinda citrifolia. L formulate leaf extract in the form of effervescent granules. Morinda citrifolia leaf extract was macerated with ethanol 96% as solvent. Phytochemical screening showsthat the extract contains flavonoids, tannins, saponins and alkaloids. The extract was formulated with various concentrations of F1 (20%), F2 (25%), F3 (4%). Determination of antioxidant activity using the DPPH free radical immersion method. The results showed that the concentration in the granules influenced antioxidant activity with IC50 values of 109.05 ppm, 101.33 ppm and 73.28 ppm, respectively